A comparative study on corrosion failure analysis of hearing aid devices from different markets. Issue 1 (20th September 2022) - Yadav, Abhijeet; Ambat, Rajan
Abstract: The vulnerability of hearing aid devices to corrosion is critical due to their exposure to various kinds of ionic contaminants from the human body, such as sweat, sebum, and so forth, and harsh climatic conditions such as high temperature, humidity, and atmospheric pollutants. The device failure rate will vary depending upon the type of geographical location at which the device is used and root cause failure analysis is a crucial tool to understand the effect of geographical location on corrosion failures. In this study, field failed hearing aid devices from Europe, the United States, and Japan markets were investigated using a scanning electron microscope and elemental dispersive spectroscopy to locate failure mechanisms and causes. Information from the analysis was used for statistical analysis to compare the performance of the devices in the three markets based on failure percentage and failure probability for different parts and components. Solder terminals, battery contacts, light‐emitting diodes, and wireless‐link coil showed consistent and high failure probability across all three markets, whereas a higher failure rate for microphones was found in Europe and the United States market as compared to the Japanese market. The majority of the components corrosion failures occurred in the presence of high chloride ions from human sweat and the atmospheric conditions, whereas potassium hydroxide from the leakage of Zn–air battery was found as the additional cause for microphone failure. Abstract : The miniaturized design trend in hearing aids has caused a tremendous reduction in sizes for electronic parts and assembly, and as a result, the robustness of the device towards corrosion‐induced failures is compromised. In this study, a large number of field‐failed hearing aid devices across different markets were analyzed to understand their failure modes and mechanisms while statistical failure analysis was performed to elucidate device failure rate and failure probability.